Evaluation of the utility of hospital databases to provide data in assessing the quality of strabismus surgery. Issue 2 (May 2013) - Heng, SJ; Low, L; MacKinnon, JR; Lavy, T; Dutton, GN
Aims and background: Rates of re-operation, which may be related to an unsatisfactory surgical outcome, can provide a long-term index of the quality of strabismus surgery. This study aims to evaluate the utility of the Scottish Morbidity Records (SMR1) in determining nature and rates of re-operation for strabismus at the Royal Hospital for Sick Children (RHSC), Glasgow. Methods: SMR1 data on strabismus surgery performed on children aged between 0 and 17 years at the RHSC, Glasgow, between January 2000 and March 2009 were analysed. Results: In total, 1376 strabismus procedures were carried out on 1274 individuals. The median time between first and subsequent procedures was 19 months; the commonest reasons being under-correction or recurrence. The Kaplan–Meier rate of undergoing re-operation was 7.4% after 9 years with a 95% confidence interval of 5.4–9.9%. Conclusions: The SMR1 is a useful source of hospital-based and population data. With supplementation from parallel databases, routine administrative databases like the SMR1 can provide better quality data to inform practice.